A multidimensional study of the structure function ratio σLT′/σ0 from hard exclusive π+ electro-production off protons in the GPD regime - S. Diehl; A. Kim; K. Joo; P. Achenbach; Z. Akbar; M.J. Amaryan; H. Atac; H. Avagyan; C. Ayerbe Gayoso; L. Baashen; L. Barion; M. Bashkanov; et al. (Physics Letters B, 2023)
A multidimensional extraction of the structure function ratio σLT′/σ0 from the hard exclusive e→p→e′nπ+ reaction above the resonance region has been performed. The study was done based on beam-spin asymmetry measurements using a 10.6 GeV incident electron beam on a liquid-hydrogen target and the CLAS12 spectrometer at Jefferson Lab. The measurements focus on the very forward regime (t/Q2 ≪ 1) with a wide kinematic range of xB in the valence regime (0.17 < xB < 0.55), and virtualities Q2 ranging from 1.5 GeV2 up to 6 GeV2. The results and their comparison to theoretical models based on Generalized Parton Distributions demonstrate the sensitivity to chiral-odd GPDs and the directly related tensor charge of the nucleon. In addition, the data is compared to an extension of a Regge formalism at high photon virtualities. It was found that the Regge model provides a better description at low Q2, while the GPD model is more appropriate at high Q2.